Interdiscurso, cenas de enunciação e ethos discursivo em canções de Ataulfo Alves - Carvalho, Fabiana Castro (2010)
This dissertation deals with the constitution of the discursive ethos, related to enunciatory scenes and interdiscourse, which are studied in four Ataulfo Alves’ songs that presented in common: The childhood’s and The hometown’s miss themes. We follow the French Discourse Analysis line in their new trends, from Maingueneau’s approach (1989, 1996, 2008) as a theoretical and methodological support, since, as this author, this theory purpose is the language studying, taking into account its externality. Our objectives were: to examine how the discursive ethos is formed, to make a deeper study on AD, to search for the samba’s role in Brazil, to know the life and the work of Ataulfo Alves taking into account its importance in MPB; to analyse four of his songs based on three notions: interdiscourse, enunciative scenes and discursive ethos, in the prospects outlined by Maingueneau for the AD. The analysis concentrated on the lyrics as an object of study, but the musical aspects were considered when they show themselves to be relevant to the ethos’s constitution. It was intended to demonstrate is that the enunciating person speaks from its place where he occupies in relation to the power that constitutes the society. After the analysis of each song, realized from the childhood and hometown themes, the results pointed to the construction of an image of himself projected into the discourse along the lines of the dominant discourse, as the enunciating person does not question the state’s ideological devices, but adjust his speech according to them. Through the interdiscursive traces we could realize that the songs were woven from the recognition of the Other, including its attachment. In addition, the construction of the scenography as a desire’s and past’s space gave to the discourse a tone of suffering that helped to build a melancholy and nostalgic ethos, resigned to the present and missing.